Methodological Aspects of the First Foreign Language for History and Archaeology Bachelors - Shkarban, Inna (Educological discourse, 2023)
The present study aims at methodological grounding of the specific types of foreign language competences for non-philology faculty students enrolled in the First Foreign Language (English) course taught within the first (bachelor) level of the academic professional program 0.32 History and Archaeology. The suggested methodological and conceptual basis outlined in the research has a concrete practical application to address university language teachers in non-philology faculties, curricula designers, professionals, researchers or practitioners in the field of foreign language teaching. The competency-based foreign language author methodology is practically exemplified in the study as a collaborative teacher-student(s) foreign language learning experience to reinforce cognitive competences through brainstorming, intellectual communication and research via formative e-learning educational and methodological complex, its development and implementation. An overall history study is essentially focused on the concept of historical thinking, specifying such cognitive skills as significance, primary source evidence, continuity and change, cause and consequence, historical perspective-taking, the ethical dimension as key research matters of academic history discourse. The fundamental meaning-making aspects of historical accounts theoretically and empirically substantiate that history and historical knowledge are always culturally predetermined, dynamic and open to contestation and discussion. Within the conceptual-methodological model, the issue is open to a broad scientific analysis in terms of cognitive competences in professional history and archaeology settings as well as in the field of competency-based foreign language learning deploying spoken and written discourse for special purposes. Pragmatic competence encompasses discursive strategies of organizing and structuring the general and professional or specialised discourse in terms of its coherence, cohesion, thematic organization, logical reasoning, as well as functional action-oriented knowledge via general or professional-oriented communicative functions performing. From the foreign language studying perspective multimodality approach has clearly envisaged as progressive constituent for further research under the competency-based foreign language learning methodology to apply in non-linguistic specialties.